2023
DOI: 10.3389/fpubh.2022.1058807
|View full text |Cite
|
Sign up to set email alerts
|

Mpox vaccination willingness, determinants, and communication needs in gay, bisexual, and other men who have sex with men, in the context of limited vaccine availability in the Netherlands (Dutch Mpox-survey)

Abstract: IntroductionIn the 2022 multicountry mpox (formerly named monkeypox) outbreak, several countries offered primary preventive vaccination (PPV) to people at higher risk for infection. We study vaccine acceptance and its determinants, to target and tailor public health (communication-) strategies in the context of limited vaccine supply in the Netherlands.MethodsOnline survey in a convenience sample of gay, bisexual and other men who have sex with men, including transgender persons (22/07-05/09/2022, the Netherla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 29 publications
4
42
1
Order By: Relevance
“…This study was conducted before the start of targeted mpox vaccination in the Netherlands and included 394 MSM [29]. These ndings were in line with another Dutch study conducted around the early roll-out of pre-exposure mpox vaccination, which showed an 81.5% vaccination acceptance [20]. A large-scale European survey observed 85-90% (northern countries) and 83-88% (western countries) intention to get vaccinated.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This study was conducted before the start of targeted mpox vaccination in the Netherlands and included 394 MSM [29]. These ndings were in line with another Dutch study conducted around the early roll-out of pre-exposure mpox vaccination, which showed an 81.5% vaccination acceptance [20]. A large-scale European survey observed 85-90% (northern countries) and 83-88% (western countries) intention to get vaccinated.…”
Section: Discussionsupporting
confidence: 83%
“…There are few studies evaluating the association between the perception of safety and vaccination intent. In a study conducted in the Netherlands, it was reported that 45.1% of people eligible for pre-exposure vaccination (PPV) and 45% of people for non-pre-exposure vaccination (non-PPV) believed that the vaccine has no unpleasant adverse effects, and this factor increased the willingness to be vaccinated against mpox [20]. In a study conducted in Ghana on the general population, one of the main determinants of vaccine acceptance was con dence in the vaccine, which increased the odds of mpox vaccine acceptance (aOR: 2.45, 95% CI, 1.93-3.15, p < 0.001) [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our findings, 59.8% of MSM living with HIV in France indicated their acceptance towards Mpox vaccination [ 41 ]. Dukers-Muijrers and colleagues found that 81.5% of the MSM surveyed in the Netherlands were willing to receive an Mpox vaccine [ 42 ]. However, the willingness rate of Mpox vaccination varied among different populations and regions [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to chronic underfunding, which has been exacerbated by the COVID-19 pandemic, sexual health clinics have served as a logical, low-barrier setting for individuals seeking MPX prevention. However, they may not be prepared for the challenge of responding to an emerging infectious disease while providing their usual services [ 58 ].…”
Section: Discussionmentioning
confidence: 99%